Towards Developing the Smart Cultural Heritage Management of the French Colonial Villas in Hanoi, Vietnam - Doan Minh, Khoi; Bui , Ngoc Phuong; Doan, Thu Minh (International Journal of Sustainable Construction Engineering and Technology, 2021)
Hanoi city was formed and inherited a unique urban heritage. Among them are the French-colonial Villas, which were constructed in the preâ€“1954 period. During the development process, the local government and community have always paid special attention to these heritage sites and organized many conservation and research activities. However, the management and preservation of these sites are still facing many challenges under pressure from urbanization, environmental impact, leading to the risk of being invaded and destroyed. The objective of this paper is to discuss the potential of developing the management strategy for French colonial villas in Hanoi within contemporary society using the concept of the Smart Cultural Heritage. The authors believe that will support various cultural services as well as promoting and preserving cultural heritage. It does so by presenting the results of the survey of the status of villas in the French period in Hanoi to classify and evaluate establish the regulation of use management and value conservation, build up the Big Data system. At the same time, the proposal will use smart platforms and participatory processes to encourage community access to raise awareness and assess the villas’ value.